2005
DOI: 10.1002/gepi.20100
|View full text |Cite
|
Sign up to set email alerts
|

Genome scans with gene‐covariate interaction

Abstract: Genetic models for gene-covariate interactions are described. Methods of linkage analysis that utilize special features of these models and the corresponding score statistics are derived. Their power is compared with that of simple genome scans that ignore these special features, and substantial gains in power are observed when the gene-covariate interaction is strong. Quantitative trait mapping in randomly ascertained sibships and affected sibpair mapping are discussed. For the latter case, a simpler statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…However, purely for mathematical convenience, we have assumed that on the latent scale, there was no interaction between the gene at the putative location and the covariate. Actually, recent developments published by Peng et al [20] explicitly account for such interactions and these authors have derived the corresponding score test for linkage. The gene by covariate interaction could be explicitly incorporated into the GLMM model in a similar way (via the R matrix of variance-covariance of random effects) and the corresponding test would obtain analogously.…”
Section: Discussionmentioning
confidence: 99%
“…However, purely for mathematical convenience, we have assumed that on the latent scale, there was no interaction between the gene at the putative location and the covariate. Actually, recent developments published by Peng et al [20] explicitly account for such interactions and these authors have derived the corresponding score test for linkage. The gene by covariate interaction could be explicitly incorporated into the GLMM model in a similar way (via the R matrix of variance-covariance of random effects) and the corresponding test would obtain analogously.…”
Section: Discussionmentioning
confidence: 99%
“…introduced a quite different model for continuous covariates. Peng, Tang and Siegmund [2005] suggested a model for gene × covariate effects for arbitrary covariates (which appears to reduce to the model of Towne et al for binary covariates) and derived the appropriate robust score tests. In this section we discuss the score test for general pedigrees.…”
Section: Extensions To the Basic Variance Component Modelmentioning
confidence: 99%
“…Overall, Peng et al [14] found that if the influence of the genecovariate interaction is negligible, there can be a loss in power by including the covariates, roughly equivalent to a 25% loss in sample size. This is caused by the additional degrees of freedom for the covariates.…”
Section: Coding Covariatesmentioning
confidence: 99%
“…Further work by Peng et al [14] showed that correctly modeling gene-covariate interaction in ASP studies can lead to substantially increased power to detect linkage, in contrast to analyses that ignore the covariates. In contrast to our approach that considers how covariates affect the mean IBD sharing, Peng et al derived score tests for linkage in ASP data by starting with a penetrance model for the joint effects of a genotype and a covariate on the phenotype.…”
Section: Coding Covariatesmentioning
confidence: 99%
See 1 more Smart Citation